Effect of a diabetes education program on adult patients in the outpatient clinic of a peruvian national hospital - Paz-Ibarra, José (2020)
Introduction. Type 2 diabetes is a public health problem whose management is very complex, recognizingmultiple problems and limitations for an adequate control of the disease. Objective. To determine the effect of educational program added to the usual treatment, in the control of patients with type 2 diabetes in a peruvian national hospital. Methods. A longitudinal analytical study of three months of follow-up was conducted. Fifty consecutive patients with uncontrolled type 2 diabetes who were treated in the outpatient clinical of the endocrinology service agreed to voluntarily participate in the four sessions in groups of 5-8 participants (1session/week). The availability of antidiabetic medication was assured, as well as the maintenance of the prescribed pharmacological doses from three months before the intervention and during the follow-up period. Changes in HbA1c levels, fasting blood glucose and lipid profile were determined before and 3 months after the intervention. Results. Of the total of patients who agreed to participate, 41 completed all sessions and their results were analyzed. The fourth part were males. After three months of the educational intervention: HbA1c decreased -1,7%, fasting blood glucose -59mg/dL and LDL cholesterol -23mg/dL; being the significant changes in the groups of over 45 years and with more than 5 years of diagnosis. Conclusions. The diabetes educational program added to the usual management had an early beneficial effect in the control of patients with type 2 diabetes in a peruvian national hospital.